2016
DOI: 10.1148/radiol.2015151466
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced Parkinsonism versus Idiopathic Parkinson Disease: Utility of Nigrosome 1 with 3-T Imaging

Abstract: Purpose To explore the utility of nigrosome 1 with 3-T magnetic resonance (MR) imaging to differentiate idiopathic Parkinson disease (IPD) from drug-induced parkinsonism (DIP). Materials and Methods The institutional review board approved this study, and participants gave informed consent. This study enrolled patients with DIP (n = 20) and IPD (n = 29) who underwent N-3-fluoropropyl-2-β-carbomethoxy-3-β-(4-iodophenyl)nortropane ((18)F-FP-CIT) positron emission tomography (PET) and healthy participants (n = 20)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 31 publications
1
70
2
1
Order By: Relevance
“…) . Subsequent studies using 3T MRI have also been able to replicate this finding in most PD patients (refer to Table for list of studies) . This replication has generated considerable interest to use nigrosome imaging as a way of studying and diagnosing nigral pathology in PD.…”
Section: Nigrosome Imagingmentioning
confidence: 80%
“…) . Subsequent studies using 3T MRI have also been able to replicate this finding in most PD patients (refer to Table for list of studies) . This replication has generated considerable interest to use nigrosome imaging as a way of studying and diagnosing nigral pathology in PD.…”
Section: Nigrosome Imagingmentioning
confidence: 80%
“…The 3 studies each included subjects with APDs or subjects with parkinsonism and normal dopaminergic radiotracer imaging . Data on these subjects with non‐PD parkinsonism were not included in the meta‐analysis because of an insufficient number of studies (≥4 studies needed for the meta‐analysis as described later), but analyzed descriptively.…”
Section: Methodsmentioning
confidence: 99%
“…Most patients with PD or other types of neurodegenerative parkinsonism studied so far lack DNH at least unilaterally (see Fig. A) . Although current evidence thus suggests that this novel MRI feature may be a marker for PD, available studies have mostly involved small samples and had heterogeneous control populations.…”
mentioning
confidence: 99%
“…Because nigrosome-1 is a histological concept, which refers to a calbindin-negative subregion in the SNc, the descriptive terms ‘Dorsolateral Nigral Hyperintensity’ (DNH) or ‘Nigral hyperintensity’ have been introduced (Reiter et al 2015; Bae et al 2016). Overall, in the studies published so far, loss of DNH had a high sensitivity (79–100%) and specificity (85–100%) to separate PD from controls (Schwarz et al 2014; Reiter et al 2015; Bae et al 2016; Kim et al 2016; Sung et al 2016). Moreover, a recent meta-analysis including 364 patients with PD and 331 controls from 10 studies showed an overall sensitivity and specificity of the absence of DNH for PD vs. controls of 98 and 95% and of 95 and 94% when including studies performed at 3.0 T only (Mahlknecht et al 2017).…”
Section: Diagnosis Of Pdmentioning
confidence: 99%
“…This meta-analysis demonstrates a potential value in differentiating PD from uncertain movement disorders such as DIP, ET and dystonic tremor. Indeed, a recent study reported that patients with DIP could be discriminated from those with PD with high sensitivity and specificity (Sung et al 2016), while loss of DNH seems not to discriminate between PD and atypical parkinsonism due to MSA and PSP (Reiter et al 2015; Bae et al 2016; Kim et al 2016). …”
Section: Diagnosis Of Pdmentioning
confidence: 99%